An investigation of froth stability in reverse flotation of collophane. (15th August 2020) - Liu, Shunbing; Ge, Yingyong; Fang, Ji; Yu, Jun; Gao, Qin
Highlights: Finer particles and increasing mineral content enhanced froth stability in reverse flotation of collophane. Calcite and dolomite promoted froth stability, while quartz had little influence in reverse flotation of collophane. The fine calcite and dolomite and the dissolved Ca 2+ and Mg 2+ stabilized the froth structure. desliming, by means of sedimentation and flotation, is the most feasible means to regulate the froth stability. Abstract: In flotation, froth stability strongly influences the separation process, as such stability is linked to the particle size, mineral content and water quality. In this study, the froth stability in the reverse flotation of collophane was investigated by froth stability tests and froth drainage experiments with the cationic surfactant N1-(3-((8-Methylnonyl)oxy)propyl)propane-1, 3-diamine (MOPPD). The results indicated that the presence of fine fractions lead to the high froth stability, and the froth stability increased with increases in the mineral content. Furthermore, it was shown that the presence of calcite and dolomite greatly increased the froth stability compared to quartz and fluorapatite. In addition, Ca 2+ and Mg 2+ dissolved by calcite and dolomite were proved to stabilize the froth structure. On the basis of the froth stability in the reverse flotation of collophane, a strategy for controlling the froth stability through desliming by sedimentation and flotation before quartz removal was proposed. Flotation tests showed that the concentrate grade increased to 28.06% and the froth volume of tailings greatly decreased to 920 mL compared with the values of 24.13% and 4200 mL, respectively, for direct flotation. Overall, the results confirmed that the proposed strategy is crucial for managing froth during quartz removal from collophane.